Overview of Target Enrichment Strategies. Issue 1 (1st October 2015) - Kozarewa, Iwanka; Armisen, Javier; Gardner, Andrew F.; Slatko, Barton E.; Hendrickson, C.L.
Abstract: Target enrichment is commonly used in next generation sequencing (NGS) workflows to eliminate genomic DNA regions that are not of interest for a particular experiment. By only targeting specific regions such as exons, one can obtain greater depth of DNA sequencing coverage for regions of interest or increase the sampling numbers of individuals, thereby saving both time and cost. This overview of target enrichment strategies provides a high‐level review of distinct approaches to capture specific sequences: (a) hybridization‐based strategies, (b) transposon‐mediated fragmentation (tagmentation), (c) molecular inversion probes (MIPs), and (d) singleplex and multiplex polymerase chain reaction (PCR) target enrichment. Strategies for assay design and performance criteria are also discussed. Other platforms currently in development are also briefly described. © 2015 by John Wiley & Sons, Inc.